2019
DOI: 10.1177/0192512119873075
|View full text |Cite
|
Sign up to set email alerts
|

How power-sharing includes and excludes non-dominant communities: Introduction to the special issue

Abstract: As the introduction to the special issue titled Democratisation in Divided Places: Designing Power-Sharing Institutions for Broad Inclusion, this article situates the themes, issues, and findings of the issue in a broad disciplinary perspective. Drawing from theories of constitutional design, peacebuilding, democratisation, and ethnonational accommodation, the article outlines the trade-offs that power-sharing faces in war-to-peace transitions and the implications for non-dominant groups. We articulate what we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Even though the literature identifies the pitfalls of securitizing displacement crises and their victims (Greenhill, 2010; Jacobsen, 2002), few public opinion studies challenge these claims or point to potential pro-peace attitudes among IDPs. To address this gap, our article highlights the exclusion-amid-inclusion (EAI) dilemma (Agarin and McCulloch, this issue), probing the potential role of IDPs as peace agents (rather than as unconditional or occasional spoilers). We argue that what is missing in the Cyprus talks is not only designated IDP representation at the official level but also other inclusive procedures involving, for instance, the inclusion of IDP representatives (including those in the diaspora) in specialized technical committees on implementing the right of return and individual consultation with property owners through new census technologies as to their preferences on return, restitution, and overall settlement provisions.…”
Section: Intergroup Relations and Internally Displaced Personsmentioning
confidence: 99%
“…Even though the literature identifies the pitfalls of securitizing displacement crises and their victims (Greenhill, 2010; Jacobsen, 2002), few public opinion studies challenge these claims or point to potential pro-peace attitudes among IDPs. To address this gap, our article highlights the exclusion-amid-inclusion (EAI) dilemma (Agarin and McCulloch, this issue), probing the potential role of IDPs as peace agents (rather than as unconditional or occasional spoilers). We argue that what is missing in the Cyprus talks is not only designated IDP representation at the official level but also other inclusive procedures involving, for instance, the inclusion of IDP representatives (including those in the diaspora) in specialized technical committees on implementing the right of return and individual consultation with property owners through new census technologies as to their preferences on return, restitution, and overall settlement provisions.…”
Section: Intergroup Relations and Internally Displaced Personsmentioning
confidence: 99%
“…Thus, while consociational settlements such as the Good Friday Agreement have been widely welcomed, they have also generated an extensive literature that is critical of their capacity to bridge the gap between communities in conflict (see, for example, Dixon, 2018;Taylor, 2006;Wilford, 2010;Wilson, 2009). It is also widely acknowledged that since by their very nature such settlements give privileged status to certain cultural segments (those between which power is formally shared), they necessarily, and ironically, undermine the status of others, resulting in an outcome that has been labelled 'exclusion amid inclusion' and is the subject of a growing literature (Agarin & McCulloch, 2020;Agarin, McCulloch, & Murtagh, 2018). It has also found its way into the legal literature in the case of Bosnia and Herzegovina (Stojanović, 2018).…”
Section: Intermediate Groups In Divided Societiesmentioning
confidence: 99%
“…The literature on conflict resolution and power-sharing in multi-ethnic societies suggested that political representation has precluded minority incorporation into the power regime and the broader political system (Agarin and McCulloch, 2020;McCulloch, 2014). From this perspective, a sustainable democracy could only be achieved through power-sharing arrangements (Noel, 2005), and power-sharing political institutions and legal means to balance interests of minorities and majorities in multiethnic societies might ease ethnic Wolff, eds., Managing and Settling Ethnic Conflicts, 1st ed.…”
Section: Summary Of the Findings And Argumentsmentioning
confidence: 99%